Neoadjuvant radiotherapy combined with targeted and immune therapies achieves a pathological complete response in borderline resectable gallbladder cancer: a case report and literature review - Li, Tao; Li, Zhiqin; Li, Keren; Li, Gong; Li, Guangxin; Zhao, Ying (Frontiers in Oncology, 2025)
BackgroundGallbladder cancer, a malignant tumor with a notable prevalence, is primarily treated with surgical R0 resection, which remains the most efficacious therapeutic strategy. Achieving this level of resection is particularly challenging for patients diagnosed at intermediate or advanced stages. Numerous clinical studies focusing on preoperative translational therapies, predominantly those utilizing chemotherapy, have substantiated their capacity to increase surgical resection and survival rates of patients with gallbladder cancer, despite the persistently low rate of R0 resection. The emergence of targeted therapies and immune checkpoint inhibitors (ICIs) in the postchemotherapy era, in conjunction with localized radiotherapy, has led to promising outcomes in preoperative treatment studies across a spectrum of solid tumors.CaseThis article describes a case of gallbladder cancer that was deemed critically resectable and confirmed pathologically through fine-needle aspiration biopsy. The patient underwent a novel regimen of preoperative radiotherapy complemented by targeted therapy with lenvatinib and immune checkpoint inhibitors (ICIs), specifically a PD-1 inhibitor. Eight weeks postradiotherapy, a radical surgical procedure was conducted, culminating in R0 resection and the attainment of complete pathological remission.ConclusionThis case underscores the potential of integrating radiotherapy with targeted therapies and ICIs as a translational treatment approach capable of facilitating successful R0 resection in patients with critically resectable gallbladder cancer, with the added benefit of achieving complete pathological remission.